1996
DOI: 10.1046/j.1365-2249.1996.d01-877.x
|View full text |Cite
|
Sign up to set email alerts
|

Raised anti-endothelial cell autoantibodies (AECA), but not anti-neutrophil cytoplasmic autoantibodies (ANCA), in recurrent oral ulceration: modulation of AECA binding by tumour necrosis factor-alpha (TNF-α) and interferon-gamma (IFN-γ)

Abstract: SUMMARYRecurrent oral ulceration (ROU) is a common oral mucosal condition of unknown etiology. However, there is evidence to suggest that vasculitis may play a role. Here we investigate the presence in ROU of two autoantibodies associated with vasculitis, AECA and ANCA. AECA target as yet unidentified antigens on the endothelial cell surface and have been identified in patients with vasculitic disorders and inflammatory conditions with a vasculitic component. ANCA target specific neutrophil-associated proteins… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0
1

Year Published

1999
1999
2019
2019

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 32 publications
0
8
0
1
Order By: Relevance
“…Healy et al . observed the presence of raised levels of antiendothelial cell antibodies, lending support to the hypothesis that a vasculitic process may underlie RAS 14 . Some authors indicated that lymphokine‐induced killer activity was decreased in RAS compared with controls.…”
Section: Discussionmentioning
confidence: 55%
See 1 more Smart Citation
“…Healy et al . observed the presence of raised levels of antiendothelial cell antibodies, lending support to the hypothesis that a vasculitic process may underlie RAS 14 . Some authors indicated that lymphokine‐induced killer activity was decreased in RAS compared with controls.…”
Section: Discussionmentioning
confidence: 55%
“…Several studies indicate that RAS is an immunopathological disorder. Numerous authors investigated immune status and response in patients with RAS 12–15 . Sistig et al .…”
Section: Discussionmentioning
confidence: 99%
“…In vasculitides, it was suggested that endothelium was not only the target of injury, but also an active participant of vasculitic damage [9]. Anti-endothelial cell antibodies (AECA) have been described in various autoimmune and vasculitic disorders [10][11][12][13][14][15][16][17][18]. They have been implicated in the pathogenesis of vascular injury common to these disorders.…”
Section: Introductionmentioning
confidence: 99%
“…Activation of the immune system in aphthous lesions and in peripheral blood was observed in RAU (3–13). Tissue‐specific autoimmunity is one of the most probable mechanisms of RAU development, with possible activation of Th1 lymphocyte profile of cytokine production (8, 14–17). There is also evidence suggesting that polymorphonuclear leukocytes (PMN) play a role in the pathogenesis of RAU (18–21).…”
mentioning
confidence: 99%